2005
DOI: 10.1099/vir.0.80734-0
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on hepatitis C virus NS5A–SH3 domain interactions: identification of residues critical for binding and implications for viral RNA replication and modulation of cell signalling

Abstract: The NS5A protein of hepatitis C virus has been shown to interact with a subset of Src homology 3 (SH3) domain-containing proteins. The molecular mechanisms underlying these observations have not been fully characterized, therefore a previous analysis of NS5A-SH3 domain interactions was extended. By using a semi-quantitative ELISA assay, a hierarchy of binding between various SH3 domains for NS5A was demonstrated. Molecular modelling of a polyproline motif within NS5A (termed PP2.2) bound to the FynSH3 domain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Firstly, we have previously shown that AP-1 inhibition via the Ras-ERK pathway is blocked both by NS5A alone and also by the full-length HCV polyprotein. Secondly, we have recently demonstrated (Macdonald et al, 2005) that AP-1 activation is also inhibited in cells harbouring the FK5.1 replicon and that this block is abrogated by mutation of an SH3 domain-binding polyproline motif in NS5A (a mutation that also abrogates Grb2 binding). One discrepancy that needs to be clarified is the reported ability of the Core protein to stimulate multiple MAPK pathways (Fukuda et al, 2001;Erhardt et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we have previously shown that AP-1 inhibition via the Ras-ERK pathway is blocked both by NS5A alone and also by the full-length HCV polyprotein. Secondly, we have recently demonstrated (Macdonald et al, 2005) that AP-1 activation is also inhibited in cells harbouring the FK5.1 replicon and that this block is abrogated by mutation of an SH3 domain-binding polyproline motif in NS5A (a mutation that also abrogates Grb2 binding). One discrepancy that needs to be clarified is the reported ability of the Core protein to stimulate multiple MAPK pathways (Fukuda et al, 2001;Erhardt et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…First, we needed to confirm that the replicon could tolerate insertions at this location. Therefore, the EGFP-coding region flanked by short hinge regions was amplified by PCR (primer sequences available upon request) and ligated into the BsaBI site of pLRM(wt) (Macdonald et al, 2005), a plasmid containing an NsiI-NsiI fragment (nt 3682-7122) of pFK5.1neo (Krieger et al, 2001). The modified NsiI-NsiI fragment was then reintroduced into pFK5.1neo, generating pFK5.1neo EGFP (Fig.…”
mentioning
confidence: 99%
“…The luciferase activity value measured in the HVRd1-luc mutant was almost the same as that of the wild-type replicon statistically. It has been demonstrated that the PxxP motif that binds to the SH3 domain may be involved in enhancing the replication efficiency or infectivity (Bliska, 1996;Macdonald et al, 2005;Pudupakam et al, 2011). A distinctive characteristic of the HVRd1 mutant is the number of proline-rich (PxxP) motifs.…”
Section: Discussionmentioning
confidence: 99%